Gross anatomy, myoarchitecture, and ultrastructure of the heart ventricle in the haemoglobinless icefish Chaenocephalus aceratus - Harrison, P.; Zummo, G.; Farina, F.; Tota, B.; Johnston, I. A. (Canadian Journal of Zoology, 1991)
The gross and microscopic anatomy of the heart ventricle in the haemoglobinless icefish Chaenocephalus aceratus is described. The ventricle is saclike in shape and has a relative mass approximately three times greater than that of related "red-blooded" Antarctic fish. The myocardium in C. aceratus is entirely trabecular and consists of myocytes, granulated noncontractile cells, and electron-dense interstitial spaces. Blood supply is through the venous lacunary circuit. In addition, two size classes of channels occur in the subepicardium, with mean diameters of 15 and 50 μm. The larger channels are connected directly with the intertrabecular spaces. The volume density of mitochondria is 0.47 in icefish myocytes, 0.15 in those of a tropical fish (Astronotus ocellatus) with a myoglobin-rich ventricle, and 0.27 in a cold-temperate fish (Cyclopterus lumpus) with a myoglobin-poor ventricle. The volume density of myofibrils in C. aceratus (0.25) is significantly less than in A. ocellatus (0.45) and C. lumpus (0.42). The data obtained are discussed in relation to present knowledge about the function of the heart in C aceratus as a low-speed, large-volume pump.